Gonadal axis hormones heterogeneity in obese adolescent boys - I. L. Nikitina; I. A. Kelmanson; N. I. Vtornikova; E. Yu. Vasilyeva (Лечащий Врач, 2025)
Background. Obesity is a multifactorial disease caused both by internal and external factors. Adolescents are more vulnerable to external risk factors and are more likely to be obese. The incidence of obesity is growing worldwide. Patients having obesity due to excessive calorie consumption are now considered to be a heterogeneity group in terms of eating behavior, emotional status and sleep quality. The obesity clinical pattern in males is quite distinctive. Thus, it was reasonable to expand our knowledge of obesity heterogeneity in terms of sex hormone levels in adolescent boys.Objective. The study was aimed to examine the heterogeneity of gonadal axis hormones in adolescent boys with obesity using cluster analysis.Materials and methods. The study involved 84 adolescents aged 14-17 years: 57 with obesity (code E66.0, ICD-10) and 27 practically healthy individuals. The anthropometrics included weight and height measurement and body mass index evaluation. Kisspeptin, testosterone, luteinizing (LH) and follicle-stimulating (FSH) hormones levels were determined. The k-means cluster analysis was used utilizing the Hartigan-Wong algorithm.Results. four clusters of observations were identified. The first cluster can be described as intact central stimulation with impaired peripherical effect. The second one was the reflection of the normal hormonal status showing median level of kisspeptin, physiological levels of LH and FSH and high level of testosterone. The third cluster showed central hyperstimulation pattern followed by lower levels of testosterone. The fourth cluster had no signs of both stimulation and effect. The majority of clinically healthy children belonged to the second, "normal" cluster. Assigning patients to any cluster compared to the second one was a significant predictor of hormones levels abnormality.Conclusion. Kisspeptin, testosterone, LH and FSH levels showed heterogeneity and were associated both with BMI deviation and age.